Outcome of chronic kidney disease patients with COVID-19 infection under maintenance dialysis: a retrospective observational study - Pandey, Bimal; Neupane, Rasik; Chapagain, Sudeep; Basnet, Prabina; Paudyal, Buddhi; Ranjitkar, Nora; Lama, Mipsang (Journal of General Practice and Emergency Medicine of Nepal, 2022)
Introduction: Chronic Kidney Disease is an important risk factor for severe COVID. Emerging evidence suggests that CKD is a key risk factor for mortality in patients with COVID-19. In this article we explore the outcomes of CKD patients with COVID19 infection further.Method: This was a retrospective observational study conducted in the dialysis unit of Department of Internal Medicine of Patan Academy of Health Sciences. All CKD patients under maintenance hemodialysis diagnosed with PCR positive COVID-19 from July 2021 to July 2022 were included in the study. The exclusion criteria were the patients newly diagnosed acute kidney injury on CKD patient with COVID-19 and COVID-19 positive patients with just antigen testing. The primary outcome of the study was in-hospital mortality. 101 patients were reviewed for this studyResult: Majority of the patients were male (73%). 42.57% of those admitted required ICU, 64.35% recovered and mortality was 35.64%.Conclusion: CKD requiring maintenance dialysis is associated with adverse outcomes in patients with COVID-19.